George Orwell's Shooting an Elephant: Ambivalent Mentality of Colonizer (Dibyajyoti Journal, 2025)
Aftermath of Second World War a wave of national independent movement started against British colonialism in the world politics. Different political uprisings and movements broke out in different Asian and African countries. This study scrutinizes Orwell's autobiographical essay Shooting an Elephant along with the theoretical tool of Reader Response theory representing colonial mentality of imperial rule. Orwell fails to comprehend the positive response of Burmese native people despite his anti-colonial view against British Raj in Burma. Reader cannot notice any unbiased perception of Burmese people as he goes through the text. The narrator presents a wrong impression about the Burmese people as he describes them as nasty creatures, people of crowed and scornful faces minimizing their anthropological and separate identities.